Surface free energy of composite materials with high calcium carbonate filler content - Rudawska, A.; Jakubowska, P.; Kloziński, A. (Polimery, 2021)
The adhesive properties of ternary composites based on middle density polyethylene (PE-MD) and isotactic polypropylene (i-PP) with high content (48–64 wt %) of inorganic fillers were studied. As fillers two kinds of calcium carbonate were used. Two fillers differed in their fineness degree and one of them had also stearic acid modified surface. It was stated that the kind and amount of filler affect mean value and scatter of surface free energy (γS) as well as its polar and dispersive components. More stable adhesive properties were observed for composites with stearic acid modified filler.